2008
DOI: 10.1590/s2179-83972008000200011
|View full text |Cite
|
Sign up to set email alerts
|

Segurança e efetividade da enoxaparina versus heparina não-fracionada no tratamento de pacientes submetidos a implante eletivo de stents não-farmacológicos: resultados imediatos e tardios

Abstract: 3 vezes ocorreu em 2 pacientes, ambos no G2-ENO (p = 0,25). Não ocorreram morte, AVE ou RU nos dois grupos. Os níveis do fator anti-Xa no G2-ENO revelaram boa anticoagulação (AC) nas duas fases: após 10 minutos, a média foi de 1,21 ± 0,23 UI/ml (0,73-1,68 Ul/ml) e no final da intervenção percutânea, foi de 1,04 ± 0,23 UI/ml (0,56-1,61 UI/ml). Na FT, 24% dos pacientes do G1-HNF e 31,5% dos pacientes do G2ENO apresentaram EC (p = 0,12). CONCLUSÕES: A utilização da ENO durante intervenção percutânea eletiva foi t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In summary, while the study by Centemero et al 11 does not give definitive answers on the safety and efficacy of IV enoxaparin in elective PCI, it does provide valuable incremental information, especially about antiXa activity following IV bolus enoxaparin. Previous studies, including STEEPLE, have shown that IV enoxaparin can be safely given to low risk patients undergoing elective PCI.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…In summary, while the study by Centemero et al 11 does not give definitive answers on the safety and efficacy of IV enoxaparin in elective PCI, it does provide valuable incremental information, especially about antiXa activity following IV bolus enoxaparin. Previous studies, including STEEPLE, have shown that IV enoxaparin can be safely given to low risk patients undergoing elective PCI.…”
mentioning
confidence: 93%
“…In the current issue of Revista Brasileira de Cardiologia Invasiva, Centemero et al 11 provide additional insight into the safety and efficacy of IV enoxaparin in elective PCI. The authors describe their single center, prospective, open label, observational experience with consecutive patients receiving IV enoxaparin (0.75 mg/kg; n = 57) for elective PCI, in comparison to their experience with IV UFH (100 IU/kg; n = 143) in similar patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation